2014
DOI: 10.1371/journal.pone.0104090
|View full text |Cite
|
Sign up to set email alerts
|

Sinupret Activates CFTR and TMEM16A-Dependent Transepithelial Chloride Transport and Improves Indicators of Mucociliary Clearance

Abstract: IntroductionWe have previously demonstrated that Sinupret, an established treatment prescribed widely in Europe for respiratory ailments including rhinosinusitis, promotes transepithelial chloride (Cl−) secretion in vitro and in vivo. The present study was designed to evaluate other indicators of mucociliary clearance (MCC) including ciliary beat frequency (CBF) and airway surface liquid (ASL) depth, but also investigate the mechanisms that underlie activity of this bioflavonoid.MethodsPrimary murine nasal sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 32 publications
2
69
0
1
Order By: Relevance
“…During exposure, the medium was changed as described above without inhibitors. Measurements of TMEM16A Cl Ϫ activity in HASM cells: current-voltage (I-V) relationships of Cl Ϫ channels of air or Cl2-exposed HASM cells were recorded in the whole cell mode of the patch-clamp technique as described recently (79). During the experiments, cells were perfused at a rate of 1 ml/min with an external solution of the following ionic composition (in mM): 145 CsCl, 2 MgCl 2, 2 CaCl2, 5.5 glucose, 10 HEPES, pH 7.4 (1 N CsOH).…”
Section: Methodsmentioning
confidence: 99%
“…During exposure, the medium was changed as described above without inhibitors. Measurements of TMEM16A Cl Ϫ activity in HASM cells: current-voltage (I-V) relationships of Cl Ϫ channels of air or Cl2-exposed HASM cells were recorded in the whole cell mode of the patch-clamp technique as described recently (79). During the experiments, cells were perfused at a rate of 1 ml/min with an external solution of the following ionic composition (in mM): 145 CsCl, 2 MgCl 2, 2 CaCl2, 5.5 glucose, 10 HEPES, pH 7.4 (1 N CsOH).…”
Section: Methodsmentioning
confidence: 99%
“…There were also parallel reductions in the expression of the enzyme cyclooxygenase-2, which forms pro-inflammatory prostaglandin E 2 . Zhang et al [7] showed that Sinupret promotes transepithelial chloride transport, and enhances ciliary beat frequency and airway surface liquid depth. Taken together, these activities would tend to enhance mucus clearance.…”
Section: Discussionmentioning
confidence: 99%
“…One of these preparations is the complex herbal medicine Sinupret which is based on gentian, evening primrose, elder, verbena and sorrel. This herbal medicine has been shown to enhance ciliary activity in vitro [7] and to have anti-inflammatory activity in animal experiments [8]. It has a wide spectrum of pharmacological properties, including secretolytic, secretomotoric, antiviral, anti-inflammatory, and immunomodulatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…Mucosal thickening has been described after experimental acute sinusitis (bacterial Staphylococcus aureus induction) in an animal model (rabbits) [15]. However, potential therapeutic effects of Sinupret on mucociliary clearance via the recently described mechanisms of hydration of airway surface liquid and stimulation of ciliary beat frequency [10,12] were not assessed in our model which focused on histological alterations. It can therefore be concluded that the herbal medicinal product Sinupret® partially prevents atrophy of the olfactory epithelium present in the course of acute experimental rhinitis in rats.…”
Section: Discussionmentioning
confidence: 99%
“…The herbal medicinal product Sinupret®, composed of Gentianae radix, Primulae flos cum calycibus, Sambuci flos, Rumicis herba and Verbenae herba, is frequently used for the treatment of acute or chronic rhinosinusitis [6,7] due to its pleiotropic effects directed against viral replication [8], bacterial infection, and inflammation [9]. In addition, its beneficial impact on mucociliary clearance was demonstrated in vivo in mice and in in vitro experiments using respiratory epithelial cells [10][11][12].…”
Section: Introductionmentioning
confidence: 99%